The TNF-α rs361525 and IFN-γ rs2430561 polymorphisms are associated with liver cirrhosis risk: a comprehensive meta-analysis - Zheng, Minghui; Li, Jing; Fang, Weizhen; Luo, Ling; Ding, Rui; Zeng, Hua; Luo, Hong; Lin, Xianghua; Duan, Chaohui (Frontiers in Immunology, 2023)
Background: Inflammation serves as an essential driver of liver cirrhosis (LC) incidence. Accordingly, a meta-analysis was carried out to explore the association between specific polymorphisms in the interferon-γ (IFN-γ) and tumor necrosis factor-α (TNF-α) genes and the incidence of LC based on comparisons of genotype and allele frequencies. Objectives: To study the relationship between TNF-α rs361525 and IFN-γ rs2430561 polymorphisms and the risk of LC. Methods: A database search was performed for all studies published as of September 10, 2022. The strength of risk relationships was assessed based on odds ratios (ORs) with 95% confidence intervals (CIs). Results: Pooled analyses were conducted for one common TNF-α polymorphism (rs361525) as well as one common IFN-γ polymorphism (rs2430561). Both of these SNPs were identified as LC-related risk factors. Specifically, rs361525 was related to LC incidence in both alcoholic liver cirrhosis (OR: 1.86, 95%CI: 1.03-3.34) and hepatitis B virus (HBV)-related cirrhosis cases (OR: 1.44, 95%CI: 1.00-2.06) when using an allelic contrast model. Moreover, rs2430561 was significantly related to LC in an Asian population (OR: 1.45, 95%CI: 1.13-1.86) and in the context of HBV-related cirrhosis (OR: 1.48, 95%CI: 1.13-1.93) when using an allelic contrast model. Conclusion: These findings indicate that rs361525 and rs2430561 represent LC-related risk factors, although additional large-scale clinical and case-control studies will be vital to confirm these results.